Mesenchymal Stromal Cells Combined With Elastin-Like Recombinamers Increase Angiogenesis In Vivo After Hindlimb Ischemia - Ibáñez-Fonseca, Arturo; Rico, Ana; Preciado, Silvia; González-Pérez, Fernando; Muntión, Sandra; García-Briñón, Jesús; García-Macías, María-Carmen; Rodríguez-Cabello, José Carlos; Pericacho, Miguel; Alonso, Matilde; Sánchez-Guijo, Fermín (Frontiers in Bioengineering and Biotechnology, 2022)
Hindlimb ischemia is an unmet medical need, especially for those patients unable to undergo vascular surgery. Cellular therapy, mainly through mesenchymal stromal cell (MSC) administration, may be a potentially attractive approach in this setting. In the current work, we aimed to assess the potential of the combination of MSCs with a proangiogenic elastin-like recombinamer (ELR)-based hydrogel in a hindlimb ischemia murine model. Human bone marrow MSCs were isolated from four healthy donors, while ELR biomaterials were genetically engineered. Hindlimb ischemia was induced by ligation of the right femoral artery and mice were intramuscularly injected with ELR biomaterial, 0.5x106 MSCs or the combination, and compared also to untreated animals. Tissue perfusion was monitored by Laser Doppler perfusion imaging. Histological analysis of hindlimbs were performed after Hematoxylin & Eosin staining. Immunofluorescence with anti-human mitochondria antibody was used for human MSC detection and the biomaterial was detected by elastin staining. To analyze the capillary density, immunostaining with an anti-CD31 antibody was performed. Our results show that the injection of MSCs significantly improves tissue reperfusion from day 7 (p=0.0044) to day 21 (p=0.0216), similarly to the infusion of MSC+ELR (p=0.0038, p=0.0014), without significant differences between both groups. After histological evaluation, ELR hydrogels induced minimal inflammation in the injection sites, showing biocompatibility. MSCs persisted with the biomaterial after 21 days, both in vitro and in vivo. Finally, we observed a higher blood vessel density when mice were treated with MSCs compared to control (p<0.0001), but this effect was maximized and significantly different to the remaining experimental conditions when mice were treated with the combination of MSCs and the ELR biomaterial (p<0.0001). In summary, the combination of an ELR-based hydrogel with MSCs may improve the angiogenic effects of both strategies on revascularization of ischemic tissues.